Time Pressure’s Impact on Jam Koma and Academic Stress in Undergraduate Students - Aini, Rohana Nur; Kesuma, Muhammad Ramadhani; Ariswati, Lusiana Desy; Henrika S., Margareth; Widaryo, Chandika Mahendra; Irianto, Ellen D. Oktanti (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research explores the effects of time pressure on cognitive fatigue, known locally as jam koma, and academic stress among undergraduate students in Samarinda, Indonesia, incorporating age and gender as control variables. Utilizing a cross-sectional survey approach, data were gathered from 150 undergraduate students through validated instruments assessing perceived time pressure, cognitive fatigue, and academic stress levels. Linear regression analyses demonstrated that time pressure exerts a significant influence on both cognitive fatigue and academic stress, whereas age and gender showed negligible impacts. These results highlight the critical role of time pressure in undermining student well-being, emphasizing the need for institutional measures such as time management workshops and mental health support programs. The culturally distinctive jam koma phenomenon offers fresh perspectives on cognitive exhaustion within Indonesia’s academic landscape, enriching global discussions on student mental health. By addressing these findings, universities can foster more supportive academic frameworks, mitigating the adverse effects of time pressure. This study bridges local and international scholarship, advocating for culturally informed interventions to enhance student resilience and productivity.